Nonlinear rotor dynamics of 2D molecular array: topology reconstruction - Lykah, V.A.; Syrkin, E.S. (Вопросы атомной науки и техники, 2012)
Molecular layers with rotational degrees of freedom and quadrupolar interaction between linear molecules are investigated theoretically. We found earlier that alternative orientation of the molecules along and perpendicular to an axis of the rectangular lattice is preferable. Here we find the integral of motion and give the topology analysis of the possible dynamical phases and special points in the long-wave limit. We find the strong anisotropy in the angle space: directions of easy excitation ("valleys'') exist. We show the potential relief reconstruction in dependence on the adsorbed lattice anisotropy. Теоретически исследованы молекулярные слои с вращательными степенями свободы и квадрупольным взаимодействием между линейными молекулами. Мы нашли ранее, что предпочтительным является альтернативное упорядочение молекул с ориентацией вдоль и перпендикулярно оси прямоугольной решетки. Выведены уравнения движения, найден их интеграл и проведен топологический анализ возможных динамических фаз и особых точек в длинноволновом пределе. Показана сильная анизотропия в плоскости углов: существуют направления легкого возбуждения ("долины''). Мы показываем реконструкции потенциального рельефа в зависимости от анизотропии адсорбированной решетки. Теоретично досліджені молекулярні шари з обертальними ступенями свободи і квадрупольною взаємодією між лінійними молекулами. Ми знайшли раніше, що кращим є альтернативне впорядкування молекул з орієнтацією вздовж і перпендикулярно осі прямокутної гратки. Виведено рівняння руху, знайдено їх інтеграл і проведено топологічний аналіз можливих динамічних фаз і особливих точок для довгохвильової межі. Показано сильну анізотропію в площині кутів: існують напрями легкого збудження ("долини''). Ми показуємо реконструкцію потенційного рельєфу в залежності від анізотропії адсорбованої решітки.